Central δ/κ opioid receptor signaling pathways mediate chronic and/or acute suckling-induced LH suppression in rats during late lactation - Yoshihisa UENOYAMA; Miku NONOGAKI; Hitomi TSUCHIDA; Marina TAKIZAWA; Sena MATSUZAKI; Naoko INOUE; Hiroko TSUKAMURA (The Society for Reproduction and Development, 2024)
In mammals, secretion of tonic (pulsatile) gonadotropin-releasing hormone (GnRH)/luteinizing hormone (LH) is often suppressed during lactation. Suppression of GnRH/LH pulses in lactating dams is assumed to be caused by suckling stimuli and a chronic negative energy balance due to milk production. The present study aimed to investigate whether the central enkephalin-δ opioid receptor (DOR) signaling mediated the suppression of LH secretion by acute suckling stimuli and/or chronic negative energy balance due to milk production in rats during late lactation when dams were under a heavy energy demand. On postpartum day 16, the number of Penk (enkephalin mRNA)-expressing cells in the arcuate nucleus was significantly higher in lactating rats than in non-lactating control rats. Pulsatile LH secretion was suppressed in rats with chronic suckling or acute 1-h suckling stimuli 6 h after pup removal on day 16 of lactation. Central DOR antagonism significantly increased the mean LH concentrations and the baseline of LH pulses in rats with chronic suckling but not with acute suckling stimuli on day 16 of lactation. Besides, central κ opioid receptor (KOR) antagonism increased the amplitude of LH pulses in rats with the acute suckling stimuli on day 16 of lactation. These results suggest that central DOR signaling mediates the suppression of LH secretion caused by a negative energy balance in rats receiving chronic suckling during late lactation. On the other hand, central KOR signaling likely mediates acute suckling stimuli-induced suppression of LH secretion in rats during late lactation.